Exploring BUMDES accountability: Balancing expectations and reality - Desti Fitriani; Amirul Shah Md Shahbudin; Elvia R. Shauki (Cogent Business & Management, 2024)
Village-owned enterprises (VOEs), known as BUMDES in Indonesia, are heralded as pivotal for rural community welfare. Yet, they contribute only 2% to 4% to village revenues, revealing a dependency on government support. This study examines the accountability practices of BUMDES through an Institutional Logic lens, highlighting a mismatch between government expectations of financial returns and BUMDES's broader performance evaluation across financial, operational, and societal domains. Utilising a multi-case study approach, the research uncovers the coexistence of dual logics within BUMDES: one favouring social welfare, the other commercial sustainability. It is noted that BUMDES utilises various control mechanisms such as meetings, dialogues, and community involvement in implementing their programmes. Mechanisms for reporting, disclosure, performance evaluation, and assessment are also in place, though self-regulatory mechanisms are notably absent. While financial accountability is confirmed, accountability in fairness and performance remains obscure. The study advocates for regulatory enhancements to clarify BUMDES objectives and align financial and social performance indicators. It also recommends developing a structured curriculum to boost the BUMDES administrators' capabilities. Additionally, linking the programmes to a compliance-based rating system could incentivise improvement and accountability.
Keywords: 650; institutional logic; symbolic construction; material practice; accountability; BUMDES